Preparation method of pavement material based on alkali-activated fly ash glass body
By converting waste-incineration fly ash and red mud into new pavement materials based on alkali-excited fly ash glass, the problems of degradation in performance of traditional pavement materials under extreme climatic conditions and low industrial waste treatment efficiency are solved, and efficient and environmentally friendly pavement material preparation and environmental adaptability are achieved.
Patent Information
- Application Number
- CN202411820719.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional pavement materials have deteriorated performance under extreme climatic conditions, making it difficult to meet complex and changeable environmental conditions, and the treatment methods of industrial waste are inefficient and costly, which affect the environment and human health.
By converting waste-incineration fly ash and red mud into new pavement materials based on alkali-excited fly ash glass, ultrasonic treatment, nanomaterial introduction, magnetic field cooling and other technologies are used to form high-value, strong environmental adaptability and easy-to-maintenance materials.
It has achieved efficient removal of harmful substances in fly ash and improved performance, forming dense, high-strength and good toughness pavement materials to ensure long-term stability of materials and environmental safety, and at the same time solved the problems of industrial waste treatment and resource utilization.
Smart Images

Figure CN119661132A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering materials and the technical field of hazardous waste treatment, and in particular to a method for preparing a road surface material based on alkali-activated fly ash glass. Background Art
[0002] With the acceleration of urbanization and the rapid expansion of the transportation industry, road traffic volume continues to rise, which puts more stringent and diversified requirements on the performance of road engineering materials. Modern road materials must have excellent load-bearing performance to support the increasing traffic load, and also need to show excellent performance in terms of tensile strength, impact resistance and long-term durability. However, although traditional pavement materials, such as asphalt and cement concrete, meet basic traffic needs, their adaptability is insufficient when dealing with complex and changing environmental conditions. Especially under the influence of thermal expansion and contraction, chemical erosion and long-term mechanical wear under extreme climatic conditions, the performance of traditional pavement materials is very easy to decline, resulting in frequent road damage and aging problems. In addition, the repair and replacement of these materials is not only time-consuming but also costly, which seriously restricts the smooth flow of road traffic, reduces road traffic efficiency, and increases the burden on public resources.
[0003] At the same time, the treatment and resource utilization of industrial waste has become a key issue that needs to be urgently addressed in the current environmental protection field. Among them, fly ash from garbage incineration and red mud, as two major industrial wastes, contain a large amount of harmful substances. If not properly disposed of, they will pose a huge threat to the environment and human health. Traditional treatment methods, such as landfill and solidification, are not only cumbersome and costly, but also have limited effects in reducing and harmlessly treating waste. Summary of the invention
[0004] In response to the technical problems existing in the prior art, the present invention provides an innovative technology for converting industrial waste such as waste incineration fly ash and red mud into a high-value new pavement material with excellent performance, strong environmental adaptability and easy maintenance.
[0005] A method for preparing a pavement material based on alkali-activated fly ash glass comprises the following steps:
[0006] S1: preparing fly ash glass, mixing fly ash and water uniformly, removing soluble ions, taking solid phase after solid-liquid separation to obtain pretreated fly ash, mixing the pretreated fly ash and nanomaterial uniformly, adding flux to obtain molten raw material, melting the molten raw material in an inert atmosphere, and then rapidly cooling in a magnetic field environment to obtain fly ash glass;
[0007] S2: preparing thermally activated red mud, heat-treating sintered red mud to obtain thermally activated red mud;
[0008] S3: preparing dry material, wherein the dry material comprises a gel material and an aggregate, wherein the gel material is composed of the fly ash glass and the heat-activated red mud;
[0009] S4: preparing a homogeneous solution, mixing the alkali activator, the water reducing agent and the nanofibers and stirring them uniformly to obtain a homogeneous solution;
[0010] S5: preparing pavement material slurry, adding the homogenized solution into the dry material, mixing them evenly, and obtaining pavement material slurry.
[0011] Furthermore, the mass ratio of fly ash to water is 1:8-13; the soluble ion removal treatment method is ultrasonic treatment, the mode is a sweep frequency mode, the frequency is 40-80kHz, the operating temperature is 50-80°C, and the time is 0.5-1h.
[0012] Furthermore, the flux is boric acid, the nanomaterials are nano titanium dioxide and carbon nanotubes; the molten raw material composition is as follows, by mass: 60 to 80 parts of the pretreated fly ash, 10 to 20 parts of the nano titanium dioxide, 2 to 8 parts of the carbon nanotubes, and 8 to 12 parts of the boric acid; the melting treatment temperature is 750 to 850°C, and is maintained at this temperature condition for 0.5 to 0.75h.
[0013] Furthermore, the rapid cooling method is to open the discharge port at the bottom of the melting furnace to allow the heated slurry to flow into a pre-prepared water pool for rapid cooling; the magnetic field environment is a low-intensity magnetic field of 500 to 1000 Gauss, and the particle size of the fly ash glass body is less than 150 μm.
[0014] Furthermore, the heat treatment method is laser-assisted heat treatment, and the specific steps are as follows: the heat-activated red mud is treated to obtain pretreated red mud with a particle size less than 150 μm, and then the pretreated red mud is thermally activated using low, medium and high power lasers in steps, and treated under low power laser conditions of 20 to 40 kHz for 1 to 2 hours, and then treated under medium power laser conditions of 40 to 60 kHz for 3 to 4 hours, and then treated under high power laser conditions of 60 to 80 kHz for 1 to 2 hours.
[0015] Furthermore, the aggregate consists of saturated surface dry basalt sand and saturated surface dry basalt coarse aggregate, and the mass fractions of the two are 40-70% and 30-60% respectively.
[0016] Furthermore, the alkaline activator is prepared from sodium hydroxide and sodium silicate, and is characterized in that the molar ratio of the alkaline activator to the components of the gel material is as follows: the molar ratio of Na2O / SiO2 is 0.23-0.36, the molar ratio of SiO2 / Al2O3 is 2.2-3.9, and the molar ratio of H2O / Na2O is 8-13.
[0017] Furthermore, the aggregate accounts for 30-40% of the mass of the cementitious material.
[0018] Furthermore, the amount of the water reducing agent added is 0.2-0.4% of the mass of the cementitious material; and the amount of the nanofiber added is 10-15% of the mass of the cementitious material.
[0019] Furthermore, the method for preparing the pavement material slurry is to first add 1 / 2 to 2 / 3 of the homogeneous solution to the dry material, stir slowly for 5 to 10 minutes using a mortar mixer, then add the remaining homogeneous solution, and stir quickly for 3 to 5 minutes using a mortar mixer. The pavement material slurry has no stratification phenomenon and a fluidity between 150 and 200 mm.
[0020] In summary, the present invention has the following beneficial effects:
[0021] First, in the process of processing fly ash to form glass, the present invention introduces ultrasonic treatment technology to address the problem of high chloride ion content in fly ash. Compared with traditional methods, the ultrasonic treatment technology has the advantages of more thorough treatment, high efficiency, low energy consumption and environmental friendliness; the introduction of nanomaterials in the melting process enhances the chemical bonding and microstructure optimization of fly ash, improves density, strength and toughness, and can accelerate melting, promote the decomposition of harmful substances, and achieve efficient and harmless treatment and performance improvement; in the rapid cooling stage after the melting process, a magnetic field environment is applied to guide the orderly arrangement of nanomaterials and fly ash, enhance the interaction between materials, form a denser microstructure, and effectively regulate harmful substances such as heavy metals, firmly lock them in the glass to prevent leaching, and ensure the long-term stability of the material and environmental safety.
[0022] Second, the present invention uses alkali excitation technology to promote deep dissolution and reorganization of fly ash glass and heat-activated red mud under alkaline conditions, activate the aluminosilicate structure, and promote the rearrangement of elements at the molecular level to form a stable, dense, high-strength, and durable aluminosilicate network structure, which can also effectively fix heavy metals and other harmful substances. This technology not only realizes the resource utilization of fly ash and red mud, but also solves the problem of environmental pollution, with significant environmental and economic benefits.
[0023] Third, the glass structure of the fly ash treated in the present invention shows high activity after alkali excitation, but the alkali-aggregate reaction will induce expansive gel, resulting in increased internal stress, cracks and structural damage of the material, affecting durability and stability, and putting forward special requirements for aggregate selection. The chemical and mineral structure of basalt is stable, and the alkali-aggregate reactivity is extremely low, which effectively avoids expansion and cracking, ensuring the long-term stability and durability of road materials. At the same time, basalt has strong resistance to chemical corrosion and can maintain structural integrity in harsh environments, such as contact with deicing chemicals or pollutants such as motor oil and fuel. Its high hardness and high strength enable it to resist wear and erosion and maintain structural stability, which is crucial to the durability and service life of the road. In addition, basalt has abundant reserves and low mining and processing costs, making it an economical and practical choice in road construction, helping to reduce construction costs and improve economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0025] Figure 1 The present invention provides a flow chart of a method for preparing a pavement material based on alkali-activated fly ash glass. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] like Figure 1 As shown in the process flow, a method for preparing a pavement material based on alkali-activated fly ash glass comprises the following steps:
[0028] S1: preparing fly ash glass, mixing fly ash and water evenly, removing soluble ions, taking solid phase after solid-liquid separation, obtaining pretreated fly ash, mixing the pretreated fly ash and nanomaterial evenly, adding flux to obtain molten raw material, melting the molten raw material in an inert atmosphere, and then rapidly cooling in a magnetic field environment to obtain fly ash glass:
[0029] Preferably, the mass ratio of fly ash to water is 1:8-13; the soluble ion removal treatment adopts ultrasonic treatment, and the ultrasonic treatment equipment selects equipment materials with chemical corrosion resistance, the mode is sweep frequency mode, the frequency is 40-80kHz, the operating temperature is 50-80°C, and the time is 0.5-1h.
[0030] When fly ash, a solid residue, is dissolved in water, the resulting mixture is often rich in a variety of soluble ions, among which the content of chloride ions is particularly significant. Chloride ions, as a typical corrosive ion, show strong corrosiveness in a high-temperature molten state, which can corrode the metal material of the melting equipment, resulting in a significant shortening of the equipment life and a decrease in melting efficiency. In addition, if the fly ash mixture containing chloride ions is used in the preparation of road construction materials, the presence of chloride ions will not only weaken the overall strength of the pavement material, but also accelerate its aging process, thereby posing a serious threat to the safety and service life of the road. The ultrasonic treatment technology introduced in this scheme, with its unique physical effects, can produce strong cavitation, stirring and micro-jet effects during the treatment process, which can significantly increase the diffusion rate and reaction activity of ions in the solution, thereby achieving efficient removal of soluble ions. Compared with traditional water washing and alkali washing methods, ultrasonic treatment can more thoroughly remove chloride ions in fly ash, and can also show obvious advantages in treatment efficiency, energy consumption control and environmental friendliness.
[0031] Preferably, the flux is boric acid, the nanomaterials are nano titanium dioxide and carbon nanotubes; the molten raw material composition is as follows, by mass: 60 to 80 parts of the pretreated fly ash, 10 to 20 parts of the nano titanium dioxide, 2 to 8 parts of the carbon nanotubes, and 8 to 12 parts of the boric acid.
[0032] In the preparation of fly ash glass melting, the introduction of nanomaterials, due to their unique size, surface and quantum effects, not only closely combines with fly ash to enhance chemical bonding and microstructure optimization, improve density, strength and toughness, but also acts as a catalyst to reduce the melting temperature, accelerate melting, promote the decomposition of harmful substances, and achieve efficient harmless treatment and performance improvement.
[0033] Preferably, during the melting process, the inert atmosphere is provided by nitrogen or argon, the melting furnace is set to heat up to 750-850°C at a rate of 5-8°C / min and then keep warm for 0.5-0.75h, and during the melting process, a rotational viscometer is used to monitor the viscosity change of the melt in real time. The rotational viscometer is installed in the melting furnace and inserted into the melt. The rotational speed and torque sensors are used to obtain and provide data related to the fluidity of the melt, and the viscosity change of the melt is monitored in real time.
[0034] Fly ash contains highly toxic pollutants such as dioxins. High-temperature melting technology can effectively decompose and harmlessly treat them, but the presence of oxygen during the process will cause dioxins to resynthesize. Therefore, this solution controls the melting atmosphere and introduces inert gas to create low-oxygen conditions, which can not only inhibit dioxin resynthesis, reduce oxidation reactions, protect equipment, but also improve the quality of the molten product.
[0035] Preferably, the rapid cooling method is to open the discharge port at the bottom of the melting furnace to allow the heated slurry to flow into a pre-prepared water pool for rapid cooling.
[0036] Preferably, the magnetic field environment is a low-intensity magnetic field of 500 to 1000 Gauss, which acts on the carbon nanotube derivatives remaining or converted during the melting process to control their arrangement and aggregation behavior in the glass body.
[0037] When the melting process is completed and the rapid cooling stage is entered, the application of a magnetic field environment can guide the nanomaterials and fly ash materials to be arranged in an orderly manner in the melt. This arrangement not only enhances the interaction between the materials, but also promotes the formation of a denser microstructure. In addition, the magnetic field environment has a significant regulatory effect on harmful substances such as heavy metals contained in the original fly ash. It can promote the uniform distribution of these harmful substances during the melting and cooling process, and firmly lock them in the microstructure of the glass during the solidification stage, thereby effectively preventing the leaching of heavy metals and ensuring the long-term stability and environmental safety of the material.
[0038] Preferably, the product after the cooling treatment is dried, ground and sieved to obtain fly ash glass with a particle size of less than 150 μm.
[0039] S2: Preparation of thermally activated red mud: thermally treating the sintered red mud to obtain thermally activated red mud:
[0040] Preferably, the sintered red mud is crushed, washed and solid-liquid separated multiple times to remove soluble ions, and then dried, ground and sieved to obtain pretreated red mud with a particle size of less than 150 μm.
[0041] Preferably, the heat treatment is laser-assisted heat treatment, and the specific operation method is to use low, medium and high power lasers in steps to thermally activate the pretreated red mud, treat the pretreated red mud under low power laser conditions of 20 to 40 kHz for 1 to 2 hours to preliminarily heat the pretreated red mud, then treat it under medium power laser conditions of 40 to 60 kHz for 3 to 4 hours to promote the structural adjustment and chemical activation of the pretreated red mud, and then treat it under high power laser conditions of 60 to 80 kHz for 1 to 2 hours to achieve deep thermal activation of the pretreated red mud.
[0042] S3: preparing dry material, wherein the dry material comprises a gel material and an aggregate, wherein the gel material is composed of the fly ash glass and the heat-activated red mud:
[0043] Preferably, the aggregate accounts for 30-40% of the mass of the cementitious material.
[0044] Preferably, the aggregate is composed of saturated surface dry basalt sand and saturated surface dry basalt coarse aggregate, and the mass fractions of the two are 40-70% and 30-60% respectively;
[0045] Preferably, the preparation method of the saturated surface-dry basalt sand and the saturated surface-dry basalt coarse aggregate is to crush and screen the basalt to obtain basalt sand with a particle size range of 0 to 4.75 mm and basalt coarse aggregate with a particle size range of 4.75 to 10 mm, the fineness modulus of the basalt sand is 2.5 to 2.8, the basalt sand and the basalt coarse aggregate are respectively soaked in water for more than 24 hours, the basalt sand and the basalt coarse aggregate are taken out of the water, the sieve is gently shaken and the surface is gently patted with a towel, and excess water is removed through the sieve, and the surface is checked for obvious water marks to confirm that it has reached a saturated surface-dry state; a mixing tool is used to continuously stir and mix the basalt sand and the basalt coarse aggregate evenly to obtain aggregate.
[0046] The glass structure formed after fly ash treatment shows high activity alkali-induced reaction (AHR) characteristics after alkali-induced treatment, which has become a highlight of road construction. However, alkali-aggregate reaction will cause the material to produce expansive gel inside. The gel will expand after absorbing water, causing the internal stress of the material to increase, and eventually lead to cracks and structural damage. Microcracks will provide channels for other corrosive media, accelerate the corrosion process inside the material, and further affect the durability and stability of the material, which puts forward special requirements for aggregate selection. Basalt is a ferromagnesian igneous rock composed of minerals such as pyroxene, plagioclase and olivine. It has excellent chemical and mineral structure stability and extremely low alkali-aggregate reactivity. This feature effectively avoids alkali-aggregate reactions caused by high alkali content, such as expansion and cracking, and ensures the long-term stability and durability of road materials. At the same time, basalt has excellent resistance to chemical corrosion and can maintain structural integrity in sections with harsh chemical environments, such as areas where deicing chemicals are often used or may be exposed to pollutants such as motor oil and fuel. This corrosion resistance ensures the stability and reliability of road materials in these special environments. In addition, basalt has excellent mechanical properties, high hardness and high strength, which makes it resistant to wear and erosion, maintaining structural integrity and stability, which is essential to the durability and service life of roads. From an economic point of view, basalt is abundant in many areas, and the cost of mining and processing is low, making it an economical and practical choice in road construction, helping to reduce overall construction costs and improve project economic benefits.
[0047] S4: Prepare a homogeneous solution, mix the alkali activator, water reducing agent and nanofibers and stir them evenly to obtain a homogeneous solution:
[0048] Preferably, the alkaline activator is prepared from sodium hydroxide and sodium silicate, characterized in that the molar ratio of the alkaline activator to the components of the gel material is as follows: the molar ratio of Na2O / SiO2 is 0.23-0.36, the molar ratio of SiO2 / Al2O3 is 2.2-3.9, and the molar ratio of H2O / Na2O is 8-13.
[0049] Using alkali activation technology, fly ash glass and heat-activated red mud can be deeply dissolved and reorganized under alkaline conditions, activating the aluminosilicate structure, causing the elements to rearrange at the molecular level, forming a stable, dense, high-strength and durable aluminosilicate network structure, which can also effectively fix heavy metals and other harmful substances. This technology not only realizes the resource utilization of fly ash and red mud, but also solves environmental pollution problems, with significant environmental and economic benefits.
[0050] Preferably, the water reducing agent is a polycarboxylic acid high-efficiency water reducing agent, and the water reducing rate is 16-22%.
[0051] Preferably, the preparation method of the nanofibers is to evenly distribute the carbon nanotubes in a polyvinyl alcohol solution and prepare them by electrospinning technology, specifically as follows: adding polyvinyl alcohol powder with a hydrolysis degree of 88-98% to deionized water at a mass ratio of 10%-20%, stirring and heating at 60-80°C, cooling the solution to room temperature, ensuring that the solution is free of bubbles and uniform, to obtain the polyvinyl alcohol solution; slowly adding 0.5-2% of the carbon nanotubes to the polyvinyl alcohol solution, and treating with an ultrasonic disperser in a frequency range of 20-40kHz for 10-30min to ensure that the carbon nanotubes The tubes are evenly distributed in the matrix, thereby obtaining a uniformly dispersed carbon nanotube-polyvinyl alcohol mixed solution; the uniformly dispersed carbon nanotube-polyvinyl alcohol mixed solution is transferred to the syringe of the electrospinning equipment to ensure that no bubbles remain, and the electric field strength is set to 10-20 kV, the spinning distance is 15-20 cm, the solution flow rate is 0.5-2 mL / h, and the relative humidity is controlled to be 30-50%, the carbon nanotube-polyvinyl alcohol mixed solution is sprayed from the needle into fibers, the nanoscale product obtained by spinning is taken out from the receiving device, and placed in a vacuum drying oven for 24 hours to obtain the nanofibers.
[0052] Preferably, the amount of the water reducing agent added is 0.2-0.4% of the mass of the cementitious material; and the amount of the nanofiber added is 10-15% of the mass of the cementitious material.
[0053] Preferably, the preparation method of the homogenous solution combines a mixing method of ultrasonic treatment and mechanical stirring, such as using a Sonics & Materials VCX 750 with Stirring The process is implemented by using equipment such as Assembly: the alkali activator and the water reducer are mixed, the ultrasonic treatment frequency is set to 20-30kHz, the power is 100-200W, and the treatment time is 5-10min, so as to remove bubbles and reduce the viscosity of the solution to form an initial solution; then the mechanical stirring is started, the stirrer is started to stir at a low speed of 200-400rpm, and the solution temperature is controlled at 40-60°C. During this process, nanofibers are gradually added to avoid fiber agglomeration, and the stirring time is 10-20min, so as to promote the uniform dispersion of the nanofibers; then the ultrasonic treatment and the mechanical stirring are carried out simultaneously, the ultrasonic treatment power is gradually increased to 200-500W, and the frequency is maintained at 20-30kHz, the stirring speed is gradually increased to 600-1000rpm, and the duration is 20-30min; after completing the ultrasonic treatment and the mechanical stirring, the solution is stirred at a low speed of 200-400rpm until a homogeneous solution is formed.
[0054] S5: Prepare pavement material slurry, add the homogenized solution into the dry material, mix them evenly, and obtain pavement material slurry:
[0055] Preferably, a mortar mixer is used to slowly stir the gel material and the aggregate to uniformly obtain the dry material.
[0056] Preferably, the method for preparing pavement material slurry is as follows: during the low-speed stirring of the homogeneous solution, the stirring is suspended, 1 / 2 to 2 / 3 of the homogeneous solution is first added to the dry material, and a mortar mixer is used to slowly stir for 5 to 10 minutes to preliminarily adjust the fluidity of the mortar, and then the remaining homogeneous solution is added, and a mortar mixer is used to quickly stir for 3 to 5 minutes to further promote the uniform mixing of the mortar, until the surface of the mortar reaches an appropriate smoothness and wetness, and there is no stratification phenomenon, and the fluidity of the mortar is tested to ensure that the fluidity is between 150 and 200 mm to obtain the slurry.
[0057] The slurry is then poured, cured and demolded to obtain a pavement material.
[0058] Example 1
[0059] This embodiment provides a design scheme for a pavement material based on alkali-activated fly ash vitreous bodies, comprising the following steps:
[0060] S1. Preparation of fly ash glass
[0061] The fly ash and water were mixed in a mass ratio of 1:10; the frequency was set at 40 kHz, the operating temperature was set at 60°C, and the ultrasonic treatment time was 1 hour through ultrasonic sweep mode; and then the process was filtered, dried, and ground in sequence to obtain pretreated fly ash.
[0062] 60 parts of pretreated fly ash, 20 parts of nano-titanium dioxide, 8 parts of carbon nanotubes and 12 parts of boric acid were mixed and melted by mass. The melting furnace was set to heat up to 850°C at a rate of 5°C / min and kept warm for 0.5h. The discharge port at the bottom of the melting furnace was opened to allow the heated slurry to flow into a pre-prepared water pool for rapid cooling. A 1000 Gauss magnetic field was applied during the cooling process, and then dried to obtain slag, which was ball-milled and sieved to obtain fly ash glass with a particle size of less than 150μm.
[0063] S2. Preparation of thermally activated red mud
[0064] The sintered red mud is crushed, and the soluble ions are removed through multiple washing and solid-liquid separation. It is then dried, ground and sieved to obtain pretreated red mud with a particle size of less than 150μm. Laser-assisted heat treatment technology is used to thermally activate the red mud in stages using low, medium and high power lasers. The low power laser is at 30kHz and the treatment time is 1h. The medium power laser is at 50kHz and the treatment time is 3h. The high power laser is at 70kHz and the treatment time is 2h to obtain thermally activated red mud.
[0065] S3. Preparation of dry materials
[0066] The basalt is crushed, screened, saturated and dried, and mixed evenly according to the following particle size composition to form aggregate: ultrafine sand less than 0.15 mm accounts for 0.8% of the total aggregate; fine sand of 0.15-0.6 mm accounts for 12%; medium sand of 0.6-2.36 mm accounts for 15.2%; coarse sand of 2.36-4.75 mm accounts for 12%; and basalt coarse aggregate of 4.75-10 mm accounts for 60%.
[0067] 50 parts of fly ash glass and 50 parts of heat-activated red mud are mixed evenly by weight to obtain a cementitious material, and 30% of the total weight of the aggregate of the cementitious material is added and mixed evenly to obtain a dry material.
[0068] S4. Preparation of homogenous solution
[0069] Preparation of nanofibers: Add polyvinyl alcohol powder at a mass ratio of 15% to deionized water, stir and heat at 70°C, cool the solution to room temperature, slowly add 1% of the carbon nanotubes to the polyvinyl alcohol solution, and use an ultrasonic disperser to treat for 25 minutes within a frequency range of 30kHz, and use electrospinning technology to spray the obtained carbon nanotube-polyvinyl alcohol mixed solution into fibers to obtain nanofibers. The electrospinning electric field intensity is 15kV, the spinning distance is 18cm, the solution flow rate is 1mL / h, and the relative humidity is controlled at 40%.
[0070] Preparation of alkaline activator: The alkaline activator is prepared from sodium silicate and sodium hydroxide. The molar ratio of Na2O / SiO2 of the alkaline activator and each component of the gel material is 0.28, the molar ratio of SiO2 / Al2O3 is 3, and the molar ratio of H2O / Na2O is 12.
[0071] Preparation of homogeneous solution: 10% of the total mass of the cementitious material is mixed with 0.3% of the polycarboxylic acid high-efficiency water-reducing agent, and treated with a Sonics & Materials VCX 750 with Stirring Assembly ultrasonic crusher at a frequency of 25kHz and a power of 150 watts for 8 minutes to form an initial solution; then, low-speed stirring is performed at a speed of 400rpm, and the solution temperature is controlled at 50°C. During this process, 12% of the total mass of the cementitious material is gradually added with nanofibers, and stirring is continued for 15 minutes; during the mechanical stirring process, the ultrasonic treatment power is gradually increased to 400 watts, the stirring speed is increased to 800rpm, and stirring is continued for 30 minutes; then, low-speed stirring is performed at a speed of 400rpm for 6 minutes to form a homogeneous solution.
[0072] S5. Preparation of road material slurry
[0073] Use a mortar mixer to slowly mix the dry materials evenly; add 1 / 2 of the homogenous solution to the dry materials, and then stir slowly for 5 minutes; add the remaining homogenous solution and stir quickly for 5 minutes until the surface of the mortar reaches appropriate smoothness and wetness, and there is no stratification; test the fluidity of the mortar to ensure that the fluidity is between 150 and 200 mm to form a slurry.
[0074] The pavement material slurry is poured, maintained and demolded to obtain the pavement material.
[0075] Example 2
[0076] This embodiment provides a design scheme for a pavement material based on alkali-activated fly ash vitreous bodies, comprising the following steps:
[0077] S1. Preparation of fly ash glass
[0078] The fly ash and water were mixed in a mass ratio of 1:13; the frequency was set at 80 kHz, the operating temperature was set at 80°C, and the ultrasonic treatment time was 0.5 h in ultrasonic sweep mode; and then filtered, dried, and ground in sequence to obtain pretreated fly ash.
[0079] 80 parts of pretreated fly ash, 10 parts of nano-titanium dioxide, 2 parts of carbon nanotubes and 8 parts of boric acid by weight are mixed and melted, and the melting furnace is set to heat up to 750°C at a rate of 6°C / min and keep warm for 0.75h. The discharge port at the bottom of the melting furnace is opened to allow the heated slurry to flow into a pre-prepared water pool for rapid cooling. During the cooling process, a 500 Gauss magnetic field is applied, and then dried to obtain slag, which is ball-milled and sieved to obtain fly ash glass with a particle size of less than 150μm.
[0080] S2. Preparation of thermally activated red mud
[0081] The sintered red mud is crushed, and the soluble ions are removed through multiple washing and solid-liquid separation. It is then dried, ground and sieved to obtain pretreated red mud with a particle size of less than 150 μm. Laser-assisted heat treatment technology is used to thermally activate the red mud in stages using low, medium and high power lasers. The low power laser is at 40 kHz and the treatment time is 2 h. The medium power laser is at 60 kHz and the treatment time is 4 h. The high power laser is at 80 kHz and the treatment time is 1 h to obtain thermally activated red mud.
[0082] S3. Preparation of dry materials
[0083] The basalt is crushed, screened, saturated and dried, and mixed evenly according to the following particle size composition to form aggregate: ultrafine sand less than 0.15 mm accounts for 1.4% of the total aggregate; fine sand of 0.15-0.6 mm accounts for 21%; medium sand of 0.6-2.36 mm accounts for 25.6%; coarse sand of 2.36-4.75 mm accounts for 21%; and basalt coarse aggregate of 4.75-10 mm accounts for 30%.
[0084] 70 parts of fly ash glass and 30 parts of heat-activated red mud are mixed evenly by weight to obtain a cementitious material, and 40% of the total weight of the aggregate of the cementitious material is added and mixed evenly to obtain a dry material.
[0085] S4. Preparation of homogenous solution
[0086] Preparation of nanofibers: Add polyvinyl alcohol powder at a mass ratio of 15% to deionized water, stir and heat at 70°C, cool the solution to room temperature, slowly add 1% of the carbon nanotubes to the polyvinyl alcohol solution, and use an ultrasonic disperser to treat for 25 minutes within a frequency range of 30kHz, and use electrospinning technology to spray the obtained carbon nanotube-polyvinyl alcohol mixed solution into fibers to obtain nanofibers. The electrospinning electric field intensity is 15kV, the spinning distance is 18cm, the solution flow rate is 1mL / h, and the relative humidity is controlled at 40%.
[0087] Preparation of alkaline activator: The alkaline activator is prepared from sodium silicate and sodium hydroxide. The molar ratio of Na2O / SiO2 of the alkaline activator and each component of the gel material is 0.36, the molar ratio of SiO2 / Al2O3 is 3.9, and the molar ratio of H2O / Na2O is 13.
[0088] Preparation of homogeneous solution: 13% of the total mass of the cementitious material is mixed with 0.4% of the polycarboxylic acid high-efficiency water-reducing agent, and treated with a Sonics & Materials VCX 750 with Stirring Assembly ultrasonic crusher at a frequency of 25 kHz and a power of 150 watts for 8 minutes to form an initial solution; then, low-speed stirring is performed at a speed of 400 rpm, and the solution temperature is controlled at 50°C. During this process, 15% of the total mass of the cementitious material is gradually added with nanofibers, and stirring is continued for 15 minutes; during the mechanical stirring process, the ultrasonic treatment power is gradually increased to 400 watts, the stirring speed is increased to 800 rpm, and stirring is continued for 30 minutes; then, low-speed stirring is performed at a speed of 400 rpm for 6 minutes to form a homogeneous solution.
[0089] S5. Preparation of road material slurry
[0090] Use a mortar mixer to slowly mix the dry materials evenly; add 1 / 3 of the homogenous solution to the dry materials, and then stir slowly for 5 minutes; add the remaining homogenous solution and stir quickly for 5 minutes until the surface of the mortar reaches appropriate smoothness and wetness, and there is no stratification; test the fluidity of the mortar to ensure that the fluidity is between 150 and 200 mm to form a slurry.
[0091] The pavement material slurry is poured, maintained and demolded to obtain the pavement material.
[0092] Example 3
[0093] This embodiment provides a design scheme for a pavement material based on alkali-activated fly ash vitreous bodies, comprising the following steps:
[0094] S1. Preparation of fly ash glass
[0095] The fly ash and water were mixed in a mass ratio of 1:8; the frequency was set at 60 kHz, the operating temperature was set at 40°C, and the ultrasonic treatment time was 0.75 h through ultrasonic sweep mode; and then filtered, dried, and ground in sequence to obtain pretreated fly ash.
[0096] 70 parts of pretreated fly ash, 15 parts of nano-titanium dioxide, 5 parts of carbon nanotubes and 10 parts of boric acid by weight are mixed and melted, and the melting furnace is set to heat up to 800°C at a rate of 7°C / min and keep warm for 0.6h. The discharge port at the bottom of the melting furnace is opened to allow the heated slurry to flow into a pre-prepared water pool for rapid cooling. During the cooling process, a 750 Gauss magnetic field is applied, and then dried to obtain slag, which is ball-milled and sieved to obtain fly ash glass with a particle size of less than 150μm.
[0097] S2. Preparation of thermally activated red mud
[0098] The sintered red mud is crushed, and the soluble ions are removed by multiple washing and solid-liquid separation. It is then dried, ground and sieved to obtain pretreated red mud with a particle size of less than 150 μm. Laser-assisted heat treatment technology is used to thermally activate the red mud in stages using low, medium and high power lasers. The low power laser is at 20 kHz and the treatment time is 1.5 h. The medium power laser is at 40 kHz and the treatment time is 3.5 h. The high power laser is at 60 kHz and the treatment time is 1.5 h to obtain thermally activated red mud.
[0099] S3. Preparation of dry materials
[0100] The basalt is crushed, screened, saturated and dried, and mixed evenly according to the following particle size composition to form aggregate: ultrafine sand less than 0.15 mm accounts for 1% of the total aggregate; fine sand of 0.15-0.6 mm accounts for 15%; medium sand of 0.6-2.36 mm accounts for 19%; coarse sand of 2.36-4.75 mm accounts for 15%; basalt coarse aggregate of 4.75-10 mm accounts for 50%.
[0101] 60 parts of fly ash glass and 40 parts of heat-activated red mud are mixed evenly by weight to obtain a cementitious material, and 35% of the total weight of the aggregate of the cementitious material is added and mixed evenly to obtain a dry material.
[0102] S4. Preparation of homogenous solution
[0103] Preparation of nanofibers: Add polyvinyl alcohol powder at a mass ratio of 15% to deionized water, stir and heat at 70°C, cool the solution to room temperature, slowly add 1% of the carbon nanotubes to the polyvinyl alcohol solution, and use an ultrasonic disperser to treat for 25 minutes within a frequency range of 30kHz, and use electrospinning technology to spray the obtained carbon nanotube-polyvinyl alcohol mixed solution into fibers to obtain nanofibers. The electrospinning electric field intensity is 15kV, the spinning distance is 18cm, the solution flow rate is 1mL / h, and the relative humidity is controlled at 40%.
[0104] Preparation of alkaline activator: The alkaline activator is composed of sodium silicate and sodium hydroxide. The Na2O / SiO2 molar ratio of the alkaline activator and each component of the gel material is 0.23, the SiO2 / Al2O3 molar ratio is 2.2, and the H2O / Na2O molar ratio is 8.
[0105] Preparation of homogeneous solution: 9% of the total mass of the cementitious material is mixed with 0.2% of the polycarboxylic acid high-efficiency water-reducing agent, and treated with a Sonics & Materials VCX 750 with Stirring Assembly ultrasonic crusher at a frequency of 25kHz and a power of 150 watts for 8 minutes to form an initial solution; then, low-speed stirring is performed at a speed of 400rpm, and the solution temperature is controlled at 50°C. During this process, 10% of the total mass of the cementitious material is gradually added with nanofibers, and stirring is continued for 15 minutes; during the mechanical stirring process, the ultrasonic treatment power is gradually increased to 400 watts, the stirring speed is increased to 800rpm, and stirring is continued for 30 minutes; then, low-speed stirring is performed at a speed of 400rpm for 6 minutes to form a homogeneous solution.
[0106] S5. Preparation of road material slurry
[0107] Use a mortar mixer to slowly mix the dry materials evenly; add 1 / 2 of the homogenous solution to the dry materials, and then stir slowly for 5 minutes; add the remaining homogenous solution and stir quickly for 5 minutes until the surface of the mortar reaches appropriate smoothness and wetness, and there is no stratification; test the fluidity of the mortar to ensure that the fluidity is between 150 and 200 mm to form a slurry.
[0108] The pavement material slurry is poured, maintained and demolded to obtain the pavement material.
[0109] Comparative Example 1
[0110] The difference between this comparative example and Example 1 is that no alkali activation treatment is performed, that is, no alkali activator is added during the preparation of the pavement material, which is specifically reflected in step S4. The other implementation conditions are exactly the same.
[0111] S4. Preparation of homogenous solution
[0112] Preparation of nanofibers: Add polyvinyl alcohol powder at a mass ratio of 15% to deionized water, stir and heat at 70°C, cool the solution to room temperature, slowly add 1% of the carbon nanotubes to the polyvinyl alcohol solution, and use an ultrasonic disperser to treat for 25 minutes within a frequency range of 30kHz, and use electrospinning technology to spray the obtained carbon nanotube-polyvinyl alcohol mixed solution into fibers to obtain nanofibers. The electrospinning electric field intensity is 15kV, the spinning distance is 18cm, the solution flow rate is 1mL / h, and the relative humidity is controlled at 40%.
[0113] Preparation of homogeneous solution: 0.3% of the total mass of the cementitious material was mixed with a polycarboxylic acid high-efficiency water-reducing agent, and treated with a Sonics & Materials VCX 750 with Stirring Assembly ultrasonic crusher at a frequency of 25 kHz and a power of 150 watts for 8 minutes to form an initial solution; then, low-speed stirring was performed at a speed of 400 rpm, and the solution temperature was controlled at 50°C. During this process, 12% of the total mass of the cementitious material was gradually added with nanofibers, and stirring was continued for 15 minutes; during the mechanical stirring process, the ultrasonic treatment power was gradually increased to 400 watts, the stirring speed was increased to 800 rpm, and stirring was continued for 30 minutes; then, low-speed stirring was performed at a speed of 400 rpm for 6 minutes to form a homogeneous solution.
[0114] Comparative Example 2
[0115] The aggregate selection of this comparative example is different from that of Example 1, which is specifically reflected in the process of step S3, and the other implementation conditions are exactly the same.
[0116] S3. Preparation of dry materials
[0117] Aggregate preparation: The aggregate is from the Gobi material of the Devil City Gobi Desert near Wuerhe Town, Wuerhe District, Karamay City, Xinjiang Uygur Autonomous Region, and its main chemical components are silicon dioxide, magnesium oxide and calcium oxide. The Gobi material is crushed and sieved, and mixed evenly according to the following particle size composition to form aggregate: Gobi material aggregate less than 4.75 mm accounts for 40% of the total aggregate; Gobi material aggregate of 4.75-10 mm accounts for 60%.
[0118] 50 parts of fly ash glass and 50 parts of heat-activated red mud are mixed evenly by weight to obtain a cementitious material, and 30% of the total weight of the aggregate of the cementitious material is added and mixed evenly to obtain a dry material.
[0119] Comparative Example 3
[0120] The preparation method of the fly ash glass body in this comparative example is different from that in Example 1, which is specifically reflected in the process of step S1, and the other implementation conditions are exactly the same: the comparative example adopts a simple water washing method to remove soluble ions, and no nanomaterials are added during the melting process, and no magnetic field is applied during the rapid cooling process after the melting process.
[0121] S1. Preparation of fly ash glass
[0122] The fly ash and water are mixed in a mass ratio of 1:10; the mixture is mechanically stirred at a rotation speed of 1000 rpm for 2 hours, and then stirred at a rotation speed of 500 rpm for 2 hours until no bubbles are generated; and then filtered, dried, and ground in sequence to obtain pretreated fly ash.
[0123] 88 parts of pretreated fly ash and 12 parts of boric acid by weight were mixed and melted, and the melting furnace was set to heat up to 850°C at a rate of 5°C / min and kept warm for 0.5h. The discharge port at the bottom of the melting furnace was opened to allow the heated slurry to flow into a pre-prepared water pool for rapid cooling, and the slag was dried to obtain slag, which was ball-milled and sieved to obtain fly ash glass with a particle size of less than 150μm.
[0124] The differences between the main implementation conditions of each embodiment and the comparative example are shown in Table 1:
[0125] Table 1 List of test conditions for embodiments and comparative examples
[0126]
[0127] Test results and analysis
[0128] The compressive strength and tensile strength of the samples prepared in each embodiment and comparative example were tested according to the Standard for Test Methods for Mechanical Properties of Ordinary Concrete (GB / T 50081-2019), the impact resistance was tested according to the Standard for Inspection and Assessment of Highway Engineering Quality (JTGF80 / 1-2017), the freeze-thaw cycle durability was tested according to the Code for Durability Design of Concrete Structures (GB / T 50476-2019), the leaching toxicity of solid waste was tested according to the Toxicity Leaching Method of Solid Waste Sulfuric Acid and Nitric Acid Method (HJ / T299-2007), the chloride ion content was tested according to the potentiometric titration method of the Technical Standard for Detection of Building Structures (GB / T 50344-2004), the SO3 content was tested according to the Determination of SO3 Content in Cement by Inductively Coupled Plasma Atomic Emission Spectrometry (DB45 / T 1341-2016), and the potential alkali reactivity test method of aggregates (mortar bar method) (ASTM D 1444-2008) was used to determine the content of chloride ions. C1260) was used to test the expansion performance caused by alkali aggregate reaction (ASR), and the test results are shown in Table 2:
[0129] Table 2 Summary of pavement material properties prepared in various embodiments and comparative examples
[0130]
[0131] According to the strict provisions of the "Highway Asphalt Pavement Design Specification" (JTG D50-2017), ordinary road materials must have a compressive strength of more than 20 to 30 MPa, while high-grade highways have more stringent requirements. In all implementation cases of the present invention, the compressive strength of the samples exceeded the threshold of 40 MPa, fully meeting the demand for high strength of highway pavement materials to cope with high traffic volume and heavy load conditions. Similarly, the specification also points out that the tensile strength of materials such as high-strength asphalt mixtures should not be less than 3 MPa. The implementation cases of the present invention not only meet this standard, but even far exceed the specifications, and are particularly suitable for application scenarios such as highways and heavy-loaded traffic roads that require high tensile strength. As for impact resistance, although there is a lack of unified standards, it is generally required that the material does not suffer significant damage under conventional impact. In this regard, the sample of Example 1 only showed slight damage under 15J impact, which meets general requirements; Example 2 performed best under 20J impact, without obvious damage; Example 3 also performed well under 15J impact.
[0132] According to the "Highway Engineering Quality Inspection and Assessment Standard" (JTG F80 / 1-2017), the design schemes of Examples 2 and 3 are particularly suitable for highways with low-frequency heavy-duty vehicles, while Example 1 is more suitable for the impact resistance requirements of urban trunk roads and municipal roads. Durability is a key indicator for evaluating the long-term performance and environmental adaptability of pavement materials. The standard also emphasizes that the materials of high-grade highways must have excellent freeze-thaw cycle resistance. In this regard, the freeze-thaw cycle service life of Examples 2 and 3 exceeds 25 years, and Example 1 also reaches more than 20 years, both of which are suitable for highways and important trunk roads.
[0133] The samples of each embodiment of the present invention have significant results in heavy metal solidification, and their heavy metal leaching concentrations are far lower than the limit values of Class II groundwater in the Groundwater Quality Standard (GB / T 14848-2017), including Cd≤0.005mg / L, Pb≤0.01mg / L, Zn≤1.0mg / L, and Cu≤1.0mg / L. At the same time, the chloride ion and SO3 contents in all embodiments do not exceed the limit values specified in the General Portland Cement (GB175-2023), which are 0.10% and 3.5%, respectively. According to the Test Method for Potential Alkali Reactivity of Aggregates (Mortar Bar Method) (ASTM C1260), if the expansion of the sample on the 14th day of the test cycle is less than 0.10%, it is deemed to have no risk of inducing ASR (alkali aggregate reaction). In this study, the samples of all embodiments met this standard, proving that they have no potential risk of ASR.
[0134] In the comparative experiment, Comparative Example 1, which did not use alkali excitation technology, performed poorly in various performance indicators, including compressive strength, tensile strength, freeze-thaw cycle durability and impact resistance. Although Comparative Examples 2 and 3 performed relatively well, Comparative Example 2 used Gobi materials, resulting in a high ASR expansion rate. According to the ASTM C1260 standard, its expansion amount is between 0.10% and 0.20%, and there is a medium reactivity and potential expansion risk. Although Comparative Example 3 prepared fly ash glass by pre-treating fly ash with water washing and performed well in many performance indicators, its heavy metal leaching toxicity increased compared with the embodiment, which was attributed to the fact that no magnetic field was applied during the water quenching slurry process, resulting in unsatisfactory solid solution effect of heavy metals in the silicate network matrix. At the same time, the chloride ion removal rate is poor, which verifies the technical advantage of the present invention in removing soluble ions by ultrasonic treatment.
[0135] In summary, all embodiments of the present invention have demonstrated excellent pavement material performance, including high compressive strength, high tensile strength, good impact resistance and durability, as well as excellent heavy metal stabilization effect and soluble ion content that meets the standards. Among them, Example 2 performs best in various indicators, and is particularly suitable for heavy-load traffic and high-demand sections; Example 3 follows closely, and is also suitable for high-grade highways; although Example 1 is slightly inferior, it can still meet the use requirements of general high-grade roads. In practical applications, the design scheme should be reasonably selected according to specific engineering requirements and environmental conditions to ensure the reliability and durability of the pavement material in different application scenarios. The pavement material provided by the present invention can fully adapt to various road requirements from light load to heavy load, ensuring its excellent performance under different conditions.
[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a pavement material based on alkali-activated fly ash glass, characterized in that: The following steps are involved: S1: preparing fly ash glass, mixing fly ash and water uniformly, removing soluble ions, taking solid phase after solid-liquid separation to obtain pretreated fly ash, mixing the pretreated fly ash and nanomaterial uniformly, adding flux to obtain molten raw material, melting the molten raw material in an inert atmosphere, and then rapidly cooling in a magnetic field environment to obtain fly ash glass; S2: preparing thermally activated red mud, heat-treating sintered red mud to obtain thermally activated red mud; S3: preparing dry material, wherein the dry material comprises a gel material and an aggregate, wherein the gel material is composed of the fly ash glass and the heat-activated red mud; S4: preparing a homogeneous solution, mixing the alkali activator, the water reducing agent and the nanofibers and stirring them uniformly to obtain a homogeneous solution; S5: preparing pavement material slurry, adding the homogenized solution into the dry material, mixing them evenly, and obtaining pavement material slurry.
2. The method for preparing a pavement material based on alkali-activated fly ash glass according to claim 1, characterized in that: The mass ratio of fly ash to water is 1:8-13; the soluble ion removal treatment method is ultrasonic treatment, the mode is a sweep frequency mode, the frequency is 40-80kHz, the operating temperature is 50-80°C, and the time is 0.5-1h.
3. The method for preparing a pavement material based on alkali-activated fly ash glass according to claim 1, characterized in that: The flux is boric acid, the nanomaterials are nano titanium dioxide and carbon nanotubes; the molten raw material composition is as follows, by mass: 60 to 80 parts of the pretreated fly ash, 10 to 20 parts of the nano titanium dioxide, 2 to 8 parts of the carbon nanotubes, and 8 to 12 parts of the boric acid; the melting treatment temperature is 750 to 850°C, and is maintained at this temperature condition for 0.5 to 0.75h.
4. The method for preparing a pavement material based on alkali-activated fly ash glass according to claim 1, characterized in that: The rapid cooling method is to open the discharge port at the bottom of the melting furnace to allow the heated slurry to flow into a pre-prepared water pool for rapid cooling; the magnetic field environment is a low-intensity magnetic field of 500 to 1000 Gauss, and the particle size of the fly ash glass body is less than 150 μm.
5. The method for preparing a pavement material based on alkali-activated fly ash glass according to claim 1, characterized in that: The heat treatment method is laser-assisted heat treatment, and the specific steps are as follows: the heat-activated red mud is treated to obtain pretreated red mud with a particle size of less than 150 μm, and then the pretreated red mud is thermally activated using low, medium and high power lasers in steps, and the pretreated red mud is treated under low power laser conditions of 20 to 40 kHz for 1 to 2 hours, and then under medium power laser conditions of 40 to 60 kHz for 3 to 4 hours, and then under high power laser conditions of 60 to 80 kHz for 1 to 2 hours.
6. The method for preparing a pavement material based on alkali-activated fly ash glass according to claim 1, characterized in that: The aggregate consists of saturated surface dry basalt sand and saturated surface dry basalt coarse aggregate, and the mass fractions of the two are 40-70% and 30-60% respectively.
7. The method for preparing a pavement material based on alkali-activated fly ash glass according to claim 1, characterized in that: The alkaline activator is prepared from sodium hydroxide and sodium silicate, and is characterized in that the molar ratio of the alkaline activator to the components of the gel material is as follows: the molar ratio of Na2O / SiO2 is 0.23-0.36, the molar ratio of SiO2 / Al2O3 is 2.2-3.9, and the molar ratio of H2O / Na2O is 8-13.
8. The method for preparing a pavement material based on alkali-activated fly ash glass according to claim 1, characterized in that: The aggregate accounts for 30-40% of the mass of the cementitious material.
9. The method for preparing a pavement material based on alkali-activated fly ash glass according to claim 1, characterized in that: The added amount of the water reducing agent is 0.2-0.4% of the mass of the gelling material; the added amount of the nanofiber is 10-15% of the mass of the gelling material.
10. The method for preparing a pavement material based on alkali-activated fly ash glass according to claim 1, characterized in that: The method for preparing the pavement material slurry is to first add 1 / 2 to 2 / 3 of the homogeneous solution to the dry material, stir slowly for 5 to 10 minutes using a mortar mixer, then add the remaining homogeneous solution, and stir quickly for 3 to 5 minutes using a mortar mixer. The pavement material slurry has no stratification phenomenon and a fluidity between 150 and 200 mm.